ANALISIS KESALAHAN BERBAHASA DAN PERANANNYA DALAM PEMBELAJARAN BAHASA ASING - Saadah, Fina (Kopertais Wilayah X Jawa Tengah, 2012)
Abstract:Errors made by second/foreign language learner occur when the learner has not learnt some of the language items then consistently gets them wrong. Some experts see errors normal as unseparated part of language learning process, while others consider them as a form of deviation which shows learner’s failure to apply the language system. The sources of errors may come from interference (learner’s first language influence), the target language complexity, or teaching and learning system. Errors can be classified into some categories: linguistic, surface, comparative, and their effect toward communication. With its paedagogical background, error analysis comes to solve learners’ language through procedure: data collection, errors identification, errors description, errors explanation, errors classification, and evaluation. The result of error analysis can be used for many benefits, including: determining the order of teaching materials, determining linguistic materials which need special treatment and more drills and exercises, improving teaching remedially, choosing language items for evaluating or testing learners’ language proficiency, and avoiding the same errors in the future. Key words:Pembelajaran bahasa, kesalahan berbahasa, analisis kesalahan berbahasa.